BICYCLE HELMET DESIGN AND THE VIRTUAL VALIDATION OF THE IMPACT, AERODYNAMICS AND PRODUCTION PROCESS - Boshevski, Bojan; Mircheski, Ile (Facta Universitatis. Series: Mechanical Engineering, 2017)
This paper presents the development process of a bicycle helmet through individual research, creation, presentation and analysis of the results of the most important product development stages. The quality of the development and manufacturing process of the protective equipment for extreme sports is an imperative for a successful product and its flawless function. The design of the bicycle helmet is made following the rules of the design in order to create a well-founded and functional product. After creating design sketches, a virtual prototype was developed in "SolidWorks" using the required ergonomic dimensions. 3D printed model of the human head with adapted ergonomic dimensions and the designed bicycle helmet was developed in order to verify the applied ergonomic measures. The virtual model will be used as an input in the finite element analysis of the helmet impact test based on the EN1078 standard and the aerodynamic simulations executed in "SolidWorks Simulation and Flow Simulation", for verification of the impact and aerodynamic properties. Virtual testing of aerodynamic features and the ability of the bicycle helmet to allow ventilation of the user's head indicate that the helmet performs its function in the desired way. Also, the virtual prototype will be used for the production process simulation in "SolidWorks Plastics" in order to analyze the production of the bicycle helmet. The polycarbonate helmet outer shell is subject to a number of simulations for the sake of analyzing the production process in order to obtain the desired characteristics of the polycarbonate outer shell and to avoid the disadvantages that occur in the manufacturing process. The main goal of this paper is to develop a safety bicycle helmet with improved ergonomic, validation of impact, aerodynamic characteristics and production process in order to produce a high quality product for mass use.